The Impact of Anti-Tumor Necrosis Factor Alpha Therapy on Postoperative Complications in Pediatric Crohn's Disease - Dotlacil, Vojtech; Bronsky, Jiri; Hradsky, Ondrej; Frybova, Barbora; Coufal, Stepan; Skaba, Richard; Rygl, Michal (European Journal of Pediatric Surgery, 2020)
Introduction The incidence of Crohn's disease (CD) within the pediatric population is increasing worldwide. Despite a growing number of these patients receiving anti-tumor necrosis factor α therapy (anti-TNF-α), one-third of them still require surgery. There is limited data as to whether anti-TNF-α influences postoperative complications. We evaluated postoperative complications in patients who were or were not exposed to anti-TNF-α therapy in our institutional cohort.Materials and Methods A retrospective review of CD patients who underwent abdominal surgery between September 2013 and September 2018 was performed. The patients were divided into two groups based on whether they were treated with anti-TNF-α within 90 days before surgery. Thirty-day postoperative complications were assessed using Clavien–Dindo classification (D-C); this examination included surgical site infections (SSIs), stoma complications, intra-abdominal septic complications, non-SSIs, bleeding, ileus, readmission rate, and return to the operating room. Mann–Whitney U-test, Fisher's exact test, and multivariate logistic regression analyses were used for statistical analysis.Results Sixty-five patients (41 males) with a median age of 16 years (range: 7–19) at the time of operation were identified. The most common surgery was ileocecal resection in 49 (75%) patients. Forty-three (66.2%) patients were treated with anti-TNF-α preoperatively. Seven patients (11%) experienced postoperative complications. There was no statistically significant difference in postoperative complication in patients who did or did not receive anti-TNF-α before surgery (D-C minor 2.3% vs. 4.6%, p = 1; D-C major 7% vs. 9.1%, p = 1).Conclusion The use of anti-TNF-α in pediatric CD patients within the 90 days prior to their abdominal surgery was not associated with an increased risk of 30-day postoperative complications.
Keywords: pediatric surgery; Crohn's disease; anti-tumor necrosis factor α; postoperative complications; inflammatory bowel disease